2013
DOI: 10.1158/1078-0432.ccr-12-3496
|View full text |Cite
|
Sign up to set email alerts
|

EDNRB and DCC Salivary Rinse Hypermethylation Has a Similar Performance as Expert Clinical Examination in Discrimination of Oral Cancer/Dysplasia versus Benign Lesions

Abstract: Purpose Promoter hypermethylation has been recently proposed as a mean for HNSCC detection in salivary rinses. In a prospective study of a high-risk population, we showed that EDNRB promoter methylation in salivary rinses is a useful biomarker for oral cancer and premalignancy. Experimental Design Using that cohort, we evaluated EDNRB methylation status and 8 additional genes. Clinical risk assessment by expert clinicians was performed and compared with biomarker performance in the prediction of premalignant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 27 publications
1
76
0
Order By: Relevance
“…Our pooled meta-analysis of 2194 oral cancer patients and 456 controls, demonstrated p16 hypermethylation in 43% oral cancers and 5.4% normal samples (Table 1). Several studies demonstrated that normal individuals with no tobacco habits showed absence or low levels of hypermethylation [9,17,22,24]. Our studies in tobacco chewing Indian oral cancer patients demonstrated p16 hypermethylation in 34% long term tobacco users (LTTUs), 25% premalignant tissues, 65% oral cancers, 47% tumor adjacent mucosa (TAM), and 0% normal controls with no tobacco habits [9].…”
Section: P16mentioning
confidence: 55%
See 2 more Smart Citations
“…Our pooled meta-analysis of 2194 oral cancer patients and 456 controls, demonstrated p16 hypermethylation in 43% oral cancers and 5.4% normal samples (Table 1). Several studies demonstrated that normal individuals with no tobacco habits showed absence or low levels of hypermethylation [9,17,22,24]. Our studies in tobacco chewing Indian oral cancer patients demonstrated p16 hypermethylation in 34% long term tobacco users (LTTUs), 25% premalignant tissues, 65% oral cancers, 47% tumor adjacent mucosa (TAM), and 0% normal controls with no tobacco habits [9].…”
Section: P16mentioning
confidence: 55%
“…Fonseca-Silva and coworkers demonstrated p16 promoter methylation in 78% HPV-16 positive oral cancers. Hypermethylation of p16 is observed in various sites of oral cavity including tongue, lower gingiva and oral floor [8,22,[25][26][27]. Our pooled meta-analysis of 2194 oral cancer patients and 456 controls, demonstrated p16 hypermethylation in 43% oral cancers and 5.4% normal samples (Table 1).…”
Section: P16mentioning
confidence: 90%
See 1 more Smart Citation
“…Recent studies in the literature validate the use of salivary rinse for biomarker detection [29][30][31][32]. As demonstrated in the literature, the DNA samples extracted from salivary rinses showed enough quality to carry out qMSP reactions [29,30,33,34].…”
Section: Discussionmentioning
confidence: 70%
“…13,16,17 The interaction of this receptor with endothelins leads to the releasing of InsP 3 and Ca 2C as second messengers. 18 It is suggested that EDNRB gene is one of the important causes of Hirschsprung's disease (HSCR). 17 In the tumor development, transcript expression of this gene is decreased through hypermethylation of CpG-rich promoter regions resulting in alteration of ET1 signaling pathway, 19 which leads into proliferation, angiogenesis, and metastasis of tumors.…”
Section: Introductionmentioning
confidence: 99%